A further HLA‐DRB1*15 family allele – DRB1*15:112. (4th September 2016) - Street, J.; Harvey, C.; Johnson, J.; Darke, C.
Abstract : HLA‐DRB1*15:112 differs from DRB1*15:01:01:01 by one base (282G > T) in exon 2 resulting in K65N.